Sildenafil citrate in healthy and diseased hearts - Adinoyi, Seriki Samuel (Journal of Cardiology and Cardiovascular Medicine, 2021)
Sildenafil citrate is one of the frontline drugs used to manage erectile dysfunction (ED). Chemically, it is described as 1-[[3-(6,7-dihydro-1-methyl-7-oxo-3-propyl-1H –pyrazolo [4,3-d]pyrimidin-5-yl)-4 ethoxyphenyl] sulfonyl]-4-methylpiperazine citrate (C22H30N6O4 S). It is a highly selective inhibitor of cyclic guanine monophosphate-specific phosphodiesterase type-5. There had been heightened concerns following reports that sildenafil citrate may increase the risk of cardiovascular events, particularly fatal arrhythmias, in patients with cardiovascular disease. So the cardiac electrophysiological effects of sildenafil citrate have been investigated extensively in both animal and clinical studies. This article ties up the various outcomes of the investigations with a view to guiding physicians and patients that use sildenafil citrate to manage erectile dysfunction, especially as it concerns its effect on their cardiovascular function in health and in disease. Sildenafil citrate could impact negatively on ailing hearts, but on a healthy heart, there may not be any such impact, rather, it improves on heart performance as it lowers the blood pressure.